Spine–Hip BMD Discordance and Age-Dependent Divergence Between T-Scores and Z-Scores at DXA: A Cross-Sectional Study (Bangladesh Journal of Nuclear Medicine, 2026)
Background: Spine–hip bone mineral density (BMD) discordance complicates dual-energy X-ray absorptiometry (DXA) interpretation and may affect osteoporosis classification. This study assessed the prevalence of spine–hip discordance and the age-dependent divergence between T-scores and Z-scores. Methods: This cross-sectional study included 292 apparently healthy individuals who underwent DXA. BMD, T-scores, and Z-scores were analyzed at the lumbar spine, left femur, and right femur. Spine–hip discordance was defined as an absolute difference of at least 1.0 SD between the lumbar spine T-score and either femoral T-score and was categorized as minor (1.0 to